Venture capital industry in Australia: Characteristics and sustainability positioning - Siddiqui, Asif Iqbal (Curtin University, 2016)
The thesis investigates the first 25 years of the operational lifespan of the venture capital (VC) industry in Australia utilising a system approach to evaluate its characteristics and viability. Analysed issues include interfirm collaboration networks, efficient use of industry resources and industry culture as well as their implications. A special attention is given to the prospects and capability of the industry in addressing the emerging frontier of environmental, social and governance risks in investment decisions.